Hypertension prevalence, awareness, treatment and control in national surveys from England, the USA and Canada, and correlation with stroke and ischaemic heart disease mortality: a cross-sectional study. Issue 8 (30th August 2013) - Joffres, Michel; Falaschetti, Emanuela; Gillespie, Cathleen; Robitaille, Cynthia; Loustalot, Fleetwood; Poulter, Neil; McAlister, Finlay A; Johansen, Helen; Baclic, Oliver; Campbell, Norm
Abstract : Objective: Comparison of recent national survey data on prevalence, awareness, treatment and control of hypertension in England, the USA and Canada, and correlation of these parameters with each country stroke and ischaemic heart disease (IHD) mortality. Design: Non-institutionalised population surveys. Setting and participants: England (2006 n=6873), the USA (2007–2010 n=10 003) and Canada (2007–2009 n=3485) aged 20–79 years. Outcomes: Stroke and IHD mortality rates were plotted against countries' specific prevalence data. Results: Mean systolic blood pressure (SBP) was higher in England than in the USA and Canada in all age–gender groups. Mean diastolic blood pressure (DBP) was similar in the three countries before age 50 and then fell more rapidly in the USA, being the lowest in the USA. Only 34% had a BP under 140/90 mm Hg in England, compared with 50% in the USA and 66% in Canada. Prehypertension and stages 1 and 2 hypertension prevalence figures were the highest in England. Hypertension prevalence (≥140 mm Hg SBP and/or ≥90 mm Hg DBP) was lower in Canada (19·5%) than in the USA (29%) and England (30%). Hypertension awareness was higher in the USA (81%) and Canada (83%) than in England (65%). England also had lower levels of hypertension treatment (51%; USA 74%; Canada 80%) and control (<140/90 mm Hg; 27%; the USA 53%; Canada 66%). Canada had the lowest stroke and IHD mortality rates, England the highest and the rates were inversely related to the mean SBP in each country and strongly related to the blood pressure indicators, the strongest relationship being between low hypertension awareness and stroke mortality. Conclusions: While the current prevention efforts in England should result in future-improved figures, especially at younger ages, these data still show important gaps in the management of hypertension in these countries, with consequences on stroke and IHD mortality.